Pelaksanaan intervensi digitalisasi sekolah pada program sekolah penggerak di sekolah dasar - Novitasari, Ragil Ayu; Marmoah, Sri Marmoah; Budiharto, Tri Budiharo (Universitas Sebelas Maret, 2024)
Sekolah penggerak have five specific interventions for the sekolah penggerak program, namely: a consultative approach, learning with a new paradigm, data-based planning, strengthening school human resources, and school digitalization. This research aims to find out and describe the implementation of sekolah penggerak digitalization. The research approach used is descriptive qualitative research. The subjects of this research were school principals, teachers and education staff at SDIT Al Jabar Gondang Sragen. Data collection techniques in this research used interviews, observation and document study. The data analysis technique used is the Miles and Huberman data analysis technique. This research uses triangulation validation techniques and sources. The results of this research are the implementation of school digitalization at SDIT Al Jabar Gondang Sragen consisting of supporting resources, digitalconnectivity, and technology platforms.